Strategi Pedagang Pasar Dalam Mempertahankan Usaha Pasca Kebakaran - Muhammad Riza Hafizi; Mariatul Jannah (Syi`ar Iqtishadi : Journal of Islamic Economics, Finance and Banking, 2021)
This study contains the retailer strategy in sustainable business in Pasar Baru A, Palangka Raya city. This study was a field research using descriptive qualitative research methods and case study methods. The subjects of this study were nine retailer of Pasar Baru A and supported by three informants from administrator of Pasar Baru A, and three buyers in Pasar Baru A. Data analysis techniques using collection data, data reduction, data display, and conclusion drawing. The results of this study indicate that Pasar Baru A retailers can sustainable their business by implementing a marketing management strategy and a risk management strategy accurately. The strategy carried out by Pasar Baru A retailers after the fire viewed from an Islamic economic perspective has been appropriate with the Islamic marketing management strategy and Islamic risk management strategy.